Analysis of the Relationship Between Body Mass Index (BMI) and Dento-Skeletal Maturation: A Cross-Sectional Case-Control Study - Alessio Verdecchia; Inmaculada Coronado de la Torre; Ivan Menéndez Diaz; Veronica García Sanz; Yolanda García Mesa; Teresa Cobo; Vanessa Paredes Gallardo (Dentistry Journal)
Background/Objectives: The aim of this cross-sectional study was to establish if there is a relationship between body mass index (BMI) and skeletodental development in young obese patients in comparison with normal-weight patients. Methods: The sample consisted of 178 individuals (115 normal weight, 37 overweight and 26 obese), aged 6 to 16 years, with a mean biological age of 11.96 ± 2.44 years. Dental maturation (dental age) was determined by using Demerjian’s method; craniofacial growth pattern, skeletal and dental class were determined by using cephalometric measurements; skeletal maturation was determined by using Baccetti’s method. Data were statistically analyzed. Results: According to Demirjian’s method, the mean dental age of the overweight and obese subjects was significantly higher than that of the normal-weight subjects (p = 0.001 and p = 0.02, respectively). A higher rate of dental class III was detected in the overweight group (p = 0.002). Concerning cephalometric records, statistically significant differences (p = 0.018) were observed in the distribution of SNA and SNB values, higher values being found in obese subjects. No difference was detected in the distribution of the ANB angle between the groups. As regards craniofacial growth pattern, no significant differences were found between the groups. Children with obesity presented more advanced skeletal maturation, reaching statistically significant differences (p = 0.02), in comparison with the normal-weight subjects. Conclusions: In conclusion, obese children showed increased tooth and skeletal development in comparison to the normal-weight subjects. These findings may be of interest for orthodontists, who should consider weight status when performing orthodontic treatment in children and adolescents.